2022
DOI: 10.4279/pip.140002
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of nickel-doped ceria: A computational modelling study

Abstract: Cerium oxide $\text{CeO}_2$, or ceria, has gained increasing interest owing to its excellent catalytic applications. Under the framework of density functional theory (DFT), this contribution demonstrates the effect that introducing the element nickel (Ni) into the ceria lattice has on its electronic, structural, and optical characteristics. Electronic density of states (DOSs) analysis shows that Ni integration leads to a shrinkage of Ce 4$f$ states and improvement of Ni 3$d$ states in the bottom of the conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
5
2
0
Order By: Relevance
“…This can be interpreted as the appearance of a new band at 306 nm (4.06 eV and HWHM ∼ 0.65 eV) when the intensity of the initial band at 320 nm (3.87 eV and HWHM ∼ 0.85 eV) decreased. This finding correlated well with the electronic density of states (DOSs) analysis carried out by Miran and Jaf [78], which showed that Ni integration led to some shrinkage of Ce4f states.…”
Section: Characterization Of the Compositessupporting
confidence: 87%
“…This can be interpreted as the appearance of a new band at 306 nm (4.06 eV and HWHM ∼ 0.65 eV) when the intensity of the initial band at 320 nm (3.87 eV and HWHM ∼ 0.85 eV) decreased. This finding correlated well with the electronic density of states (DOSs) analysis carried out by Miran and Jaf [78], which showed that Ni integration led to some shrinkage of Ce4f states.…”
Section: Characterization Of the Compositessupporting
confidence: 87%
“…On the other side, adding cations (Pt/Ni) with different ionic radii (1.35 Å) have caused a substantial decrease in lattice constants of Pt:CeO 2 , Ni:CeO 2 , and Pt-Ni:CeO 2 . Lattice constants of Pt doped CeO 2 were obtained to be 5.14 Å which resemble with experimental work of P Panagiotopoulou et al [54] and calculated lattice constant (5.39 Å) of Ni doped CeO 2 may be compared with experimental findings of [35,36,38]. Lattice constant of Pt:CeO 2 and Ni:CeO 2 may have good comparison with experimental findings of Asha Gupta et al [55].…”
Section: Structural Propertiessupporting
confidence: 82%
“…Band gap of pure CeO 2 has good agreement with experimental work of I N Bazhukova et al [63], S Guo et al [64] and with theoretical findings of R Rami et al [61]. However, band gap of Ni doped CeO 2 may be compared with experimental study of Fazal Abbas et al [42], Z K Sani et al [41], J Zimou et al [38] and with theoretical results of Hussein A Miran and Zainab N Jaf [36]. Hence, band gap values as obtained in our computational study have great association with already reported works which validate our findings.…”
Section: Band Gapsupporting
confidence: 71%
See 1 more Smart Citation
“…Various theoretical and experimental approaches are reported in the literature to modify the band gap of ceria to enhance its visible light photocatalytic activities and energy storage applications. In this context, Miran et al studied the Ni-doped ceria under the framework of density functional theory (DFT) and the doped system demonstrated a decrement in band gap [58]. However, Khan et al reported the electron beam irradiated ceria thin films approached to narrow the optical band gap from 3.36 eV to 3.12 eV through defect engineering [59].…”
Section: Understanding the Defect Mechanismmentioning
confidence: 99%